Neurobiological Mechanisms of Chemotherapy-induced Cognitive Impairment in a Transgenic Model of Breast Cancer. (15th January 2018) - Winocur, Gordon; Berman, Hal; Nguyen, Mary; Binns, Malcolm A.; Henkelman, Mark; van Eede, Matthijs; Piquette-Miller, Micheline; Sekeres, Melanie J.; Wojtowicz, J. Martin; Yu, Johnson; Zhang, Haibo; Tannock, Ian F.
Highlights: Chemotherapy caused cognitive impairment in a transgenic mouse model of breast cancer. Tumor development independently contributed to cognitive deficits. Deficits on tests of hippocampal and frontal lobe function were accompanied by volumetric changes in these regions. Memory loss following chemotherapy was associated with suppression of hippocampal neurogenesis. Cognitive impairment in tumorigenic mice was associated with dysregulation of neuroinflammatory cytokine activity. Abstract: Animal studies have reinforced clinical reports of cognitive impairment in cancer survivors following chemotherapy but, until now, all pre-clinical research in this area has been conducted on normal rodents. The present study investigated the effects of chemotherapy on cognition and underlying biological mechanisms in the FVB/N-Tg (MMTV- neu ) 202 Mul/J mouse, a well-characterized transgenic model of breast cancer that has similarities to the tumorigenesis which occurs in humans. Tumor-bearing and control mice received three weekly injections of a combination of methotrexate + 5-fluorouracil, or an equal volume of saline. Different aspects of learning and memory were measured before and after treatment. The effects of tumor and chemotherapy on neurogenesis, neuro-inflammatory cytokine activity, and brain volume, as they relate to corresponding cognitive changes, were also measured. The toxic effects of chemotherapy extended to the cancerous model in which substantial cognitive impairment was also associated with the disease. Cognitive deficits were greatest in tumorigenic mice that received the anti-cancer drugs. Both tumor growth and chemotherapy caused significant changes in brain volume, including the hippocampus and frontal lobes, two structures that are directly implicated in cognitive tasks that were shown to be vulnerable. The level of hippocampal neurogenesis in adulthood was suppressed in chemotherapy-treated mice and associated with loss of hippocampus-controlled cognitive function. Dysregulation of cytokine activity was found in tumorigenic mice and associated with impaired cognitive performance. The results show that chemotherapy and tumor development independently contribute to cognitive deficits through different biological mechanisms.